A RETROSPECTIVE STUDY ON TWINNING AND LIVE FOALING RATES AFTER MANUAL REDUCTION IN THOROUGHBRED MARES - DINESH, N M; BALAMURUGAN, K; PARTHEBAN, P (The Indian Journal of Animal Reproduction, 2020)
Twinning is an important cause of pregnancy loss in mares, which is often associated with the economic lossto the thoroughbred industry. The rate of twinning was documented as 9% (84/890), while the live foal rate was 77%(65/84) after manual reduction. Influence of mare’s age, reproductive status, ovarian activity, number of ovulations,month of covering and mare’s repetition on twinning rates were also studied. The present study was undertaken torecord the twinning rate and live foal rates in thoroughbreds as there are no recent publications.
Keywords: Live foal rates; manual reduction; multiple ovulations; thoroughbred mares; twinning